Analysis of the epidemiological profile of arboviruses (dengue, zika and chikungunya) from 2020-2022 in Brazil (Research, Society and Development, 2023)
Brazil is experiencing an epidemic that has lasted more than 10 years, and this epidemic is caused by arboviruses. Taking this scenario into account, this article proposes to evaluate the epidemiological profile of patients who are more predisposed to being infected by Arboviruses: Dengue, Zika and Chikungunya. This is a descriptive, retrospective, quantitative study on the epidemiological profile of the arboviruses dengue, Zika and Chikungunya in Brazil between the years 2020 and 2022 through the collection and analysis of data obtained by the Notifiable Diseases Information System (SINAN ), General Coordination of Arbovirus Surveillance of the Department of Immunization and Communicable Diseases of the Health Surveillance Secretariat (CGARB/DEIDT/SVS), Ministry of Health (DATASUS) and the Health Surveillance Secretariat (SVS). Analyzes were carried out by calculating relative frequencies, absolute frequencies, means and standard deviation for the statistical interpretation of the data obtained. After evaluating the data, it was identified that the profile of the patient contracting dengue is: A patient who resides in the Southeast, in São Paulo, aged 20-39 years, of brown or white race, female, in the period between the 7th and the 20th week of the year. The other profile is shared by the two arboviruses Zika and Chikungunya, he is: A patient who resides in the Northeast, unique to Bahia, aged 20-39 years, of mixed race, female, who is in the period between 7th and 20th week.